PENGELOMPOKAN PATOTIPE Xanthomonas oryzae pv. oryzae ASAL SULAWESI TENGGARA MENGGUNAKAN PADI GALUR ISOGENIK IRRI - Syair, H; Samirin, Samirin; Wijayanto, Teguh; Khaeruni, Andi (Jurnal Agroteknos, 2012)
This Research aimed at grouping of Xanthomonas oryzae pv. oryzae pathotypes in rice cropping center of Southeast Sulawesi using isogenic lines of IRRI, as well as to know the Xanthomonas oryzae pv. oryzae pathotypes dominating and spreading in rice cropping center of Southeast Sulawesi. The pathotype grouping was determined by leaf innoculated cutting method using 30 isolates of Xanthomonas oryzae pv. oryzae from Southeast Sulawesi in 10 isogenic lines, namely IRBB1, IRBB2, IRBB3, IRBB4, IRBB5, IRBB7, IRBB10, IRBB11, IRBB13, and IRBB21. Each isolate was inoculated on the 10 isogenic lines and repeated twice. Observation  of disease intensity was conducted randomly on five leaves at four weeks after inoculation. The disease intensity was measured by the ratio of the length (cm) of leaf blight symptom to total the length of leaf sample (cm). The research results indicated there were seven pathotypes of Xanthomonas oryzae pv. oryzae in Southeast Sulawesi, i.e : pathotype X, XI, XII and four new pathotypes. Pathotype XII was the dominant pathotype, abort 79.31% of the total isolates and spreading in three regencies, Kolaka, Konawe, and South Konawe. Keywords: bacterial leaf blight, Xanthomonas oryzae pv. oryzae, pathotype